Indicated prevention with long‐chain polyunsaturated omega‐3 fatty acids in patients with 22q11DS genetically at high risk for psychosis. Protocol of a randomized, double‐blind, placebo‐controlled treatment trial. Issue 5 (24th October 2014) - Armando, Marco; De Crescenzo, Franco; Vicari, Stefano; Digilio, Maria Cristina; Pontillo, Maria; Papaleo, Francesco; Amminger, G. Paul
Abstract: Aim: It has been found that long‐chain omega‐3 polyunsaturated fatty acids (PUFAs) reduce the risk of progression to first episode of psychosis (FEP) and may offer a safe and efficacious strategy for selective and indicated prevention in young people with ultra‐high‐risk (UHR) states. An opportunity for exploring the trajectory of FEP and for investigating the efficacy of preventive treatments exists in 22q11.2 deletion syndrome (22q11DS), which has a 30% psychotic transition rate. The fact that 22q11DS patients are more homogeneous than other UHR groups and are characterized by high level of negative symptoms provides a strong rationale for the use of PUFAs. The principal aim of the present trial is to investigate the effects of PUFAs in individuals with 22q11DS who are at UHR for developing FEP. Methods: A prospective, randomized, double‐blind, placebo‐controlled, single‐centre study design will be used. Eighty individuals aged 12–26 will be randomly assigned to two treatment conditions. Results: The experimental group will receive PUFAs. The placebo group will receive paraffin oil. Standard clinical assessments and neuropsychological tests will be performed at baseline and at 8‐, 12‐, 26‐ and 52‐week follow‐up. Blood samples will be collected at baseline and after 12 weeks. This study is registered as an International Standard RCT, number 02070211. The corresponding author is supported by a NARSAD Young Investigator Award. Conclusions: This is the protocol of a planned study that aims to test the efficacy of PUFAs in the prodromal phase of FEP, in a specific syndrome where there is strong evidence that a high genetic load is involved in the disorder.